Stimulus Presentation at Specific Neuronal Oscillatory Phases Experimentally Controlled with tACS: Implementation and Applications - ten Oever, Sanne; de Graaf, Tom A.; Bonnemayer, Charlie; Ronner, Jacco; Sack, Alexander T.; Riecke, Lars (Frontiers in Cellular Neuroscience, 2016)
In recent years it has become increasingly clear that both the power and phase of oscillatory brain activity can influence the processing and perception of sensory stimuli. Transcranial alternating current stimulation (tACS) can phase-align and amplify endogenous brain oscillations and has often been used to control and thereby study oscillatory power. Causal investigation of oscillatory phase is more difficult, as it requires precise real-time temporal control over both oscillatory phase and sensory stimulation. Here, we present hardware and software solutions allowing temporally precise presentation of sensory stimuli during tACS at desired tACS phases, enabling causal investigations of oscillatory phase. We developed freely available and easy to use software, which can be coupled with standard commercially available hardware to allow flexible and multi-modal stimulus presentation (visual, auditory, magnetic stimuli, etc.) at pre-determined tACS-phases, opening up a range of new research opportunities. We validate that stimulus presentation at tACS phase in our setup is accurate to the sub-millisecond level with high inter-trial consistency. Conventional methods investigating the role of oscillatory phase such as magneto-/electroencephalography can only provide correlational evidence. Using brain stimulation with the described methodology enables investigations of the causal role of oscillatory phase. This setup turns oscillatory phase into an independent variable, allowing innovative and systematic studies of its functional impact on perception and cognition.